2021
DOI: 10.3389/fcell.2021.722953
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Lysate Maintains Stemness of Umbilical Cord-Derived Mesenchymal Stromal Cells and Promote Lung Repair in Rat Bronchopulmonary Dysplasia

Abstract: Mesenchymal stromal cells (MSCs) show potential for treating preclinical models of newborn bronchopulmonary dysplasia (BPD), but studies of their therapeutic effectiveness have had mixed results, in part due to the use of different media supplements for MSCs expansion in vitro. The current study sought to identify an optimal culture supplement of umbilical cord-derived MSCs (UC-MSCs) for BPD therapy. In this study, we found that UC-MSCs cultured with human platelet lysate (hPL-UCMSCs) were maintained a small s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We also found deviations in methylomics separating samples by donor origin and culture conditions in hPL vs. FBS, but barely by culture duration. It has also been shown that hPL-expanded cells displayed lower levels of senescence compared to cells expanded in FBS [38]. During senescence, epigenetic alterations and notably DNA methylation play an important role in shaping the expression of proliferation-related genes [39].…”
Section: Discussionmentioning
confidence: 99%
“…We also found deviations in methylomics separating samples by donor origin and culture conditions in hPL vs. FBS, but barely by culture duration. It has also been shown that hPL-expanded cells displayed lower levels of senescence compared to cells expanded in FBS [38]. During senescence, epigenetic alterations and notably DNA methylation play an important role in shaping the expression of proliferation-related genes [39].…”
Section: Discussionmentioning
confidence: 99%
“…Human umbilical cord mesenchymal stem cells were isolated and cultured as described below [ 44 ]. First, the umbilical cord was washed twice with 75% alcohol, followed by an additional two washes with Dulbecco’s phosphate-buffered saline (D-PBS); Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…hUC-MSCs were obtained and cultured according to previously described methods [ 41 ]. Briefly, the umbilical cord was obtained from a healthy pregnant woman after informed consent was obtained.…”
Section: Methodsmentioning
confidence: 99%